The antibacterial activity of trimethoprim-sulfamethoxazole in urine - March, Sandra B., 1939- (1982)
Thesis (M. Sc.)--Memorial University of Newfoundland, 1983. Medicine Bibliography: leaves 148-157. Cotrimoxazole (TMP-SMX) is a premixed combination of-the antimicrobial agents, trimethoprim (TMP) and sulfamethoxazole (SMX), in a fixed ratio. The drug has been used for the treatment of urinary tract and other infections for more than 10 years but its efficacy and the nature of its antibacterial activity have remained controversial. The present work was undertaken in an effort to clarify some of the issues which have been raised. - The antibacterial properties of the drug and its components were assessed in several in vitro systems. Synergy between TMP and SMX, one of the main arguments supporting the use of the fixed combination, was examined by drug diffusion in agar, checkerboard titration, and time-kill curves against a standard Escherichia coli strain (ATCC 25922) and against a variety of bacterial pathogens isolated from patients with urinary tract infection. Minimal inhibitory concentrations for 100 clinical isolates were established by agar dilution and the parameters by which synergy is defined were evaluated. Time-kill curves, constructed from growth in drug-supplemented broth and urine, and in urine from cotrimoxazole-treated patients, were used to assess the kinetics of antibacterial activity of TMP-SMX and its components against pathogens commonly associated with urinary tract infections. -- The results reported here indicate that TMP is the more active agent in the mixture and in many instances inhibition is afforded by the TMP component alone. In vitro synergy could be demonstrated when the test organism was sensitive to each of the components but the synergistic effect was clear only at drug levels significantly lower than those achievable in urine following usual drug dosage. Time-kill curves demonstrate the bactericidal nature of TMP-SMX activity but results with TMP alone were not markedly different. Bactericidal effects could not be detected for SMX. -- Bioassay of urine samples from cotrimoxazole-treated patients showed that TMP was the major active constituent. Only low levels of biologically active SMX were detected by assay against a TMP-resistant strain of Proteus mirabilis. The minor contribution of SMX to total antibacterial activity in urine specimens from these patients was confirmed by the addition of para-aminobenzoic acid (PABA), a known antagonist of sulfonamides. - The data presented do not support the efficacy of the fixed ratio combination in management of urinary tract infections.